Peran Masyarakat Lokal Dalam Pengelolaan Destinasi Wisata : (Study Kasus Objek Wisata Kapalo Banda Taram, Kecamatan Harau, Kabupaten Lima Puluh Kota) - Doni Ikhlas; Asdi Agustar; Ifdal (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2024)
This study discusses the role of the community in developing the Kapalo Banda tourist attraction in Nagari Taram, Fifty Cities District. The results of this study are described in several formulations of the problem, namely what local people do to the Kapalo Banda Tourism Object so that it becomes an attraction for tourists and with the development of the Kapalo Banda tourism object, what benefits do the local community get. Based on the existing problems, this study aims to describe what the local community plays in supporting the development of the Kapalo Banda tourist destination and obtain information about the benefits obtained by the local community with the development of the Kapalo Banda tourist attraction. This research is a research conducted using a combined quantitative and qualitative approach. While the research method used is a case study method using observation, interviews, and documentation. The results of this study indicate that there are five roles of the community in managing tourist destinations a) as Initiators b) as Executors c) as Participants d) as observers/supervisors e) as Beneficiaries and a tourist attraction will develop if the community is involved in the whole process. The community must play a role in developing tourism objects where the goal of increasing community welfare is a priority in developing tourism objects in tourist villages.